A Contrapuntal Reading of Arthur Golden’s Memoirs of a Geisha - Abubakar, Sadiya; A Prem, Chandr; Muhammad, Suzana (Pusat Pengajian Ilmu Kemanusiaan, 2019)
Historical overview of prostitution in Japan Until the enactment of Anti-Prostitution Law in 1956, prostitutes were safely operating as the brothel districts had been licensed since 1589. Thus they were somewhat under the Japanese government’s protection (Leupp, 2003). However, even in previous centuries before the Anti-Prostitution Law enactment, sexual variability in the form of the sexual services the brothels offer, or the prostitutes’ personal business engagements were considered completely normal and a large part of daily life (Downer, 2001). Saburuko (serving girls) is the first ever documented sex workers in Japanese history which dates back to the 759 AD as found in the ancient Japanese book Ma‘nyōshu which translates to “A Collection of Ten Thousand Leaves”. According to this record, the Saburuko (described as wanderers) came from displaced families because of factional struggles that took place in Japan during the late 600s. They wandered and resorted to prostitution for survival (Stephenson, 2018).